Cholesterol Level as Predicting of Uric Acid Increase in Elderly (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2020)
Uric acid cause inflammation accompanied deformity knees and legs. Elderly increase from 841 million in 2013 to more than 2 billion in 2050. Prevalence of uric acid in Asia regions the lowest Papua New Guinea 1% highest Marshall Islands 85% and Indonesia 18%. Uric acid is main factor predicting kidney failure. The study objective to identify risk factors for elderly uric acid in ordering impacted of volcano areas in Sleman district. Study design were used cross sectional. Population study is elderly under Pakem center health service age 50 - 95 years ordering inclusion and exclusion criteria. Sample was required 66 elderly. Blood sample 5 ml with aseptic with parameter by Easy Touch GCU. Data were collecting by 2 enumerator ordering Pakem center health service. Data were analyzed by SPSS versi 20 with statistic test linear regression with 95% Confidence interval. Mean of age 68,17±9,6 years old, body weigh 51,0±9,7 kilo, systole blood pressure 141,97±0,3 mmHg, diastolic blood pressure 75,15±10,2 mmHg, cholesterol 194,9±49,2 mg/dl, uric acid 4,9±1,3 mg/dl. Age have been predicting β = 0,056, body weigh β = 0,058, systole blood pressure β = 0,07, diastole blood pressure β = 0,08, cholesterol β = 0,21, glucose β = 0,07 being uric acid for elderly. Above normal average of blood pressure, cholesterol level, uric acid. Cholesterol level is main factor predicting of uric acid.